Impact Of The Program My Friend Iron on the nutritional lifestyle to prevent anemia - Bertha Chanducas Lozano (2019)
Objective: Determine the impact of the program “My Friend Iron” on the nutritional lifestyle to prevent anemia among the students of Human Nutrition at the Universidad Peruana Union, Lima 2006.Methodology: The design of the research was pre-experimental because it worked with a group ofstudents who submitted a questionnaire before and after the intervention program “My Friend Iron”.Results: After the application of the program “My Friend Iron,” 60,7% of the students obtained agood level of understanding, 28,6% an excellent level of understanding, and only 10,7% a regular level ofunderstanding about the theme concerned. The 100% of the students presented positive attitudes in relation to the prevention of anemia, 78,6% practiced a healthy nutritional lifestyle, 14,3% a not very healthynutritional lifestyle, and only 7,1% practiced an unhealthy nutritional lifestyle.Conclusion: The program “My Friend Iron”, had a positive impact on the nutritional lifestyle to prevent anemia in the students of Human Nutrition at the Universidad Peruana Union